Highly Effective Removal of Ciprofloxacin from Aqueous Solution Using Graphene Oxide Functionalized Zeolite - Ahmmed, Md S; Mohiuddin, A K (Journal of Engineering Science, 2025)
Graphene oxide (GO) functionalized zeolites (ZGO) was synthesized as an adsorbent for swift and successful removal of the ciprofloxacin (CIP) antibiotic. The as-prepared nanocomposite was characterized by field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), and RAMAN spectroscopy. The adsorption ability of ZGO for CIP was investigated at different pH (2-11), contact time (5-120 min), and adsorbent dosage (0.1-0.75 g L-1) to obtain the optimum condition for maximum removal percentage of target adsorbate. The results provided very fast (15 min only) highly effective removal of CIP (97.67%) for 0.25 g L-1 ZGO, while the pH of the aqueous solution was 7.0. Kinetic and isotherm analysis of this study indicated that the adsorption process happened on the multilayer and heterogeneous surface of ZGO and was carried out by a chemical reaction between CIP and ZGO. The highest adsorption capacity (qm) was calculated as 61.35 mg g-1 at 40°C, while 8.28 and 12.45 mg g-1 were at 20, and 30°C, respectively, which suggested the stimulation of greater sites of ZGO surface with the increment of temperatures during the adsorption process. Furthermore, strong stability and superior reusability of ZGO revealed that it could be a potential adsorbent for easy removal of CIP antibiotics from the aqueous solution. Journal of Engineering Science 15(2), 2024, 29-39